SEPAKBOLA DAN POLITIK : FAKTOR PSIS DALAM KETERPILIHAN YOYOK SUKAWI PADA PEMILU LEGISLATIF TAHUN 2019 - Ilham - Aminulloh; Kushandajani - -; Yuwanto - - (Journal of Politic and Government Studies, 2022)
This study discusses how PSIS as a form of social asset contributes to the election of Yoyok Sukawi in the 2019 legislative elections. The social asset discussed in this case are the resources that strengthen Yoyok Sukawi's social assets in the 2019 legislative elections. This makes it easier for Yoyok Sukawi to be able to prepare and get vote support to be able to be elected in the 2019 legislative election. This study uses a qualitative method. Data collection techniques used are structured interviews. The location of this research took place in the city of Semarang, Central Java. As supporting data, this research also uses both primary and secondary sources of data. The data analysis used includes data collection, reduction, and conclusions This research shows that the social assets owned by Yoyok Sukawi in the 2019 legislative elections, one of which puts PSIS and includes the blue panzer containing the supporters, which is the basis of his voice support. The use of supporters as targets is closely related to the close relationship that has been established by Yoyok Sukawi as CEO of PSIS Semarang. The social asset involved in this study also discusses social networks and trust as a strong source of social asset. This social asset contains the resources owned by Yoyok Sukawi and then used for materials that can be seen and assessed by his political targets, which are none other than the supporters. Social network as part of social asset is a pattern of social interaction that is intertwined repeatedly, in these social relationships there is a common goal together therefore that from this similarity can be tied with a sense of trust between each other regarding progress in Semarang. The social trust that emerged among the supporters made the two of them increasingly have a close social relationship and arise based on knowing well the individual they will choose. This study recommends that Yoyok Sukawi maintain the pattern of social relations that have been established and be able to mobilize supporters to participate in other activities besides football interests thus as to create more balance in society